Development of a Novel Recombinant Full-Length IgY Monoclonal Antibody against Human Thymidine Kinase 1 for Automatic Chemiluminescence Analysis on a Sandwich Biotin-Streptavidin Platform for Early Tumour Discovery. (17th March 2023) - Wang, Xiangbin; Li, Shan; Zhao, Rui; Li, Huijun; Gao, Peng; Jin, Cuicui; Fang, Cong; Liu, Yongping; Hei, Ailian; Zhou, Ji; Li, Jin; He, Ellen; et al.
Abstract : Serum thymidine kinase 1 protein (STK1p) concentration has been used successfully as a reliable proliferating serum biomarker in early tumour discovery and clinical settings. It is detected by an enhanced chemiluminescence (ECL) dot blot assay with the biotin-streptavidin (BSA) platform (a gold standard) based on chicken anti-human thymidine kinase 1 IgY polyclonal antibody (hTK1-IgY-pAb). However, ECL dot blotting is a semiautomatic method that has been limited to large-scale applications due to the differences among batches of antibodies from individual hens, and the skill level of operation technicians sometimes results in unstable STK1p values. Therefore, a highly stable recombinant chicken full-length IgY monoclonal antibody in combination with a fully automated sandwich biotin-streptavidin (sandwich-BSA) platform was developed. Hens were immunized with 31-peptide, a key sequence of human TK1 (hTK1), before constructing an immune phage display scFv library. Finally, a recombinant full-length IgY monoclonal antibody (hTK1-IgY-rmAb#5) with high-affinity binding with human recombinant TK1 (rhTK1) (3.95 × 10 − 10  mol/L), high sensitivity with hTK1 calibrators (slope of linear curve: 89.98), and high specificity with low/elevated STK1p (r ≈ 0.92 -0.963) was identified. hTK1-IgY-rmAb#5 showed a specific immune response with thymidine kinase 1 (TK1) in TK1-positive/negative cell lysates by Western blotting and immunohistochemistry (IHC) in normal and cancer tissues. In particular, the detection of TK1 serum samples from health centres showed a high coincidence rate (r = 0.988, n = 90 ) between hTK1-IgY-rmAb#5 and hTK1-IgY-pAb and between the semiautomatic ECL dot blot BSA platform and the novel automatic chemiluminescence sandwich-BSA platform (r = 0.857, n = 292 ). hTK1-IgY-rmAb#5 is stable and highly sensitive for detecting the lowest STK1p value at 0.01 pmol/L (pM). The accuracy is high (SD < 2.5 % ) between different batches. It is easy to use the novel hTK1-IgY-rmAb#5 on a new automatic chemiluminescence sandwich-BSA platform. It will be beneficial for large-scale health screenings.